Genetic Diversity of MHC B-F/B-L Region in 21 Chicken Populations - Yuan, Yiming; Zhang, Huanmin; Yi, Guoqiang; You, Zhen; Zhao, Chunfang; Yuan, Haixu; Wang, Kejun; Li, Junying; Yang, Ning; Lian, Ling (Frontiers in Genetics, 2021)
The chicken major histocompatibility complex (MHC) on chromosome 16 is the most polymorphic region across the whole genome, and also an ideal model for genetic diversity investigation. The MHC B-F/B-L region is 92 kb in length with high GC content consisting of 18 genes and one pseudogene (Blec4), which plays important roles in immune response. To evaluate polymorphism of the Chinese indigenous chickens as well as to analyze the effect of selection to genetic diversity, we used WaferGen platform to identify sequence variants of the B-F/B-L region in 21 chicken populations, including the Red Jungle Fowl, 16 Chinese domestic breeds, two introduced breeds, Cornish, White Leghorns, and two well-known Marek’s disease resistance/susceptability White Leghorn lines 63 and 72. A total of 6,170 SNPs and 595 INDELs in the B-F/B-L region were identified among the 21 populations, of which 4,040 SNPs (65%) and 565 INDELs (95%) were novel. Most of the variants were within the intron and the flanking regions. The average variation density was 65 SNPs and 5.8 INDELs per kb, indicating dramatical high diversity of this region. Furthermore, BF2 was identified as the hypervariable genes with 148 SNPs per kb. The Chinese domestic populations showed higher diversity than the White Leghorns and Cornish. The indigenous breeds, Naodan Yao, Gushi, and Xishuangbanna Game chickens, were the top three with the highest density of SNPs and INDELs. The highly inbred lines 63 and 72 have the lowest diversity, which might be resulted from a long-term intense selection for decades. Collectively, we refined the genetic map of chicken MHC B-F/B-L region, and illustrated genetic diversity of 21 chicken populations. Abundant genetic variants were identified, which not only strikingly expanded the current Ensembl SNP database, but also provided high-quality molecular markers for the future breeding.